Experimental Study of the Spray Characteristics of Diesohol Fuel using a High‐Pressure Common‐Rail Injection System in a Diesel Engine. Issue 9 (5th May 2015) - Song, L. B.; Lin, Q. Z.; Xie, Y. Z.; Hu, H. W.; Hu, H. Q.; Pi, D.; Xu, S. M.
Abstract The spray characteristics of diesohol fuel have a direct effect on the thermal efficiency and combustion emissions performance of diesel engines. In this research, we investigated the spray characteristics of diesohol fuel under different fuel injection pressures (Pinj) in a high‐pressure common‐rail injection system and at various spray ambient pressures (Pamb) in a constant‐volume pressure vessel by using high‐speed photography technology. The research results support the concept of adding a certain percentage of ethanol to diesel, creating diesohol fuel, which can reduce the environmental impacts of vehicle emissions. Experiments on the spray characteristics were performed and the results suggested that the addition of ethanol has no significant effect on the spray tip penetration, spray cone angle, and spray tip speed. However, atomization conditions such as injection pressure and ambient pressure have a significant impact on the spray characteristics of the blended fuel.